Final research report RAGS (RAGS15-061-0124) identifying the macroeconomic factors influencing the pricing methods of sovereign sukuk - Rahman, Maya Puspa (Research Management Centre, 2018)
Research report on the Research Acculturation Grant Scheme (RAGS) awarded in 2015. The submission of this report is the requirement for completing and closing the grant as required by the RMC and MOHE.